(3cJGH GdadGMI GdfHWjIs - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s
(3ChdgG (B:s
(3gPG cJGH GdadGMI GdfHWjI fbdg ef dSGf GdcSJGfjjf Edi GdYQHjI GYde jG Hfi Cfi hLOJ gPG GdcJGH ai LedI eG hLOJ ef cJH GdcSOGfjjf s
(3BNQgG (B:s
(3agPG gh Chd eG jchf Hg GadGM hSHH Chd Ke jJHY Pdc CTjGA cKjQI ef GdSbi hgHhH GdghGA Je GdLRA GdChd s
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B23s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1447s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs